2008
DOI: 10.1016/j.ijgo.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine versus terbutaline for tocolysis in external cephalic version

Abstract: Nifedipine can be used as an alternative for tocolysis in ECV when there are maternal contraindications to beta-sympathomimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Our findings are consistent with previous studies that have shown that terbutaline1012 and salbutamol13–15 are effective tocolytic agents accompanied by side effects. These studies show that beta-adrenergic agonists are more effective compared to calcium channel blockers;101214 however, their significant side effects have limited use in practice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with previous studies that have shown that terbutaline1012 and salbutamol13–15 are effective tocolytic agents accompanied by side effects. These studies show that beta-adrenergic agonists are more effective compared to calcium channel blockers;101214 however, their significant side effects have limited use in practice.…”
Section: Discussionsupporting
confidence: 93%
“…These studies show that beta-adrenergic agonists are more effective compared to calcium channel blockers;101214 however, their significant side effects have limited use in practice. On the other hand, these agents do not decrease the neonatal mortality and morbidity associated with PTL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This retrospective review aimed to analyse the outcome following successful ECV in our hospital. The success rate of ECV over these three years was 51.4%, which has improved compared to those reported in previous local studies [13, 14]. Hofmeyr et al demonstrated a similar success rate of ECV (40–50%) in routine clinical practice [15].…”
Section: Discussionmentioning
confidence: 56%